An Analysis of the HRD Mechanisms Employed by the Submersible Pump Manufactures in Coimbatore City - Dr. Sangeetha .P (International Journal of Engineering and Management Research, 2019)
Human Resource Development (HRD) is a continuous process of enabling and ensuring the development of employees in a systematic and planned way. No organization can grow and survive in the present day environment without growth and development of its people. Developing the human resource by upgrading their skills, extending their knowledge and competencies would lead to organizational development. Human Resource is the most important and valuable resource of every organization. Dynamic people can build dynamic organizations. Efficient employees can contribute to the effectiveness of an organization. Competent and motivated employees can make things happen and enable an organization to achieve its goal. Therefore, organizations should continuously ensure that the dynamism, competence, motivation and effectiveness of the employee always remain high. The present study is an attempt to contribute to a better understanding of the HRD climate prevailing in submersible manufacturing organizations. The general climate, HRD Mechanisms and OCTAPAC culture are better in submersible pump organizations.